Ecological Movement During Covid-19 Pandemic: Study of Living Quran at the Asy-Syarifiy Islamic Eco-Boarding School Lumajang-East Java-Indonesia - Syarifah, Ma'isyatusy; Amin, Ahmad Syaifuddin (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2022)
The ecological movement of students at the Asy-Syarifiy Pandanwangi Islamic Boarding School, Tempeh, Lumajang, East Java, Indonesia during the Covid-19 pandemic that runs the daily lives of students is very interesting to study because the Qur'an is not only read and studied as a compulsory subject for boarding schools. pesantren, but also make the Qur'an the basis for caring for the environment. The purpose of this research is to how the ecological movement in Asy-Syarfiy is, how is the actualization of the living Quran in the ecological movement in Asy-Syarfiy during the Covid-19 pandemic. The objective research of this article is descriptive qualitative research with the type of field research with the socio-religious approach of Karl Mannheim which is a sociological theory of meaning. Data collection was carried out by involving observation, documentation, and in-depth interviews in June 2021 with seven informants. This study found, firstly, that Asy-Syarifiy students have high discipline in maintaining environmental stability so that their relationship with other environmental components is balanced, especially during the pandemic. Second, students carry out the ecological movement of the Islamic boarding school by reading the verse of the chair (verse 225 of Surah Al Baqarah) every morning and evening before carrying out environmental cleaning activities for the Islamic boarding school. Third, since the pandemic, the chair verse reading activity has also been carried out after every fardhu prayer in the congregation and is read seven times because the chair verse is believed to be a form of rejecting the dangers of Covid-19. Thus, the verses of the Qur'an come alive among the students.Keywords: Ecology movement; Pandemic;